Regulation of Innovation Under Follow-On Biologics Legislation: FDA Exclusivity As An Efficient Incentive Mechanism - Morgan, Maxwell R. (Science and Technology Law Review, 2009)
As part of its broader effort to reform the American health care system, Congress has recently enacted legislation that creates a statutory pathway for FDA approval of generic “follow-on” biologics products. A crucial debate leading up to the passage of this legislation was whether and to what extent it should provide originator biologics manufacturers with a period of FDA data exclusivity protection as an incentive for future innovation. This debate was particularly significant because of the ongoing reevaluation in the United States of the appropriate role of patent law in fostering technological advance, with recent Supreme Court decisions indicating a trend towards retrenchment of the scope of available patent protections. In the end, the bill adopted by Congress and signed into law by President Obama affords manufacturers of new biologics products with 12 years of data exclusivity. The central thesis of this Article is that optimal biologics innovation policy would situate FDA exclusivity as the industry’s primary incentive mechanism, displacing patent law in that role. The inclusion of a lengthy 12-year data exclusivity period in the newly enacted legislation is a laudable step in the right direction. But reliance on patenting in the biologics innovation process would also likely have to be substantially curtailed in order to attain optimal levels of innovation. If this were achieved, FDA exclusivity would act as an adequate surrogate for the incentives offered by patents, while a number of pathologies currently associated with patenting in the biomedical research context would be eliminated. This Article also argues that Congress should adopt a regime of market exclusivity protection instead of the data exclusivity protection presently included in the new legislation. Market exclusivity would permit the FDA to adopt rules requiring public disclosure of both basic research results (which may cease to be published absent strong patent rights) and clinical trials data (which cannot be divulged under a data exclusivity regime) in exchange for FDA approval. Such disclosure rules would contribute to efficient, disaggregated research into new and improved therapeutic approaches.